APPROACH TO THE SUBSTANTIATION OF THE OPTION OF COMPOSITION OF THE METROLOGICAL OFFICE GROUPS IN CONSIDERING RISKS - Andrey S. Efremov; Sergei V. Puzankov (Измерение, мониторинг, управление, контроль, 2023)
Background. An important component of the metrological support of technical systems is the verification of measuring instruments. The procedure for verification of measuring instruments can be carried out in the places of their operation by visiting metrological groups using mobile verification laboratories and complexes. To more effectively solve the problems of metrological services, it is necessary to assess the risks that affect the work of the field metrological group. The relevance of the topic is due to the importance of tasks in making decisions on the acquisition of field metrological groups under conditions of various kinds of uncertainties. The aim of the work is to identify and analyze risk factors that affect the effectiveness of metrological services. Materials and methods. Research is based on the use of probability theory and mathematical statistics, reliability theory and qualimetry in relation to the tasks of evaluating the effectiveness of the functioning of field metrological groups. Results. The composition of indicators of effectiveness, efficiency and resource intensity for evaluating the effectiveness of the activity of field metrological groups is considered. The description of the task of determining the parameters of field metrological groups under the conditions of ensuring an acceptable level of risk is given. An analysis of the sources of hazardous events and their impact on the effectiveness of metrological services is presented. Conclusion. Using the considered approach, a number of rational or optimal options for organizing the activities of visiting metrological groups as part of departmental metrological services in the conditions of an uncertain situation can be determined.